2018
DOI: 10.1002/hup.2652
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of interleukin 6 in schizophrenic patients during treatment augmentation with sarcosine (results of the PULSAR study)

Abstract: Sarcosine does not significantly affect IL-6 concentrations but IL-6 may be involved in mechanisms related to the presence of positive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Evidence-based psychotherapies are broadly underutilized, 2 and existing data suggest that some dietary supplements are potentially useful and relatively safe. 2,3,4,5,24,25,26,27…”
Section: Discussionmentioning
confidence: 99%
“…Evidence-based psychotherapies are broadly underutilized, 2 and existing data suggest that some dietary supplements are potentially useful and relatively safe. 2,3,4,5,24,25,26,27…”
Section: Discussionmentioning
confidence: 99%
“…Along the same lines, a series of studies from the Polish Sarcosine Study in Schizophrenia (PULSAR) project illustrated that schizophrenic patients treated with sarcosine for 6 months displayed significant improvements in negative symptoms, general psychopathology and changes in glutamatergic transmission in the brain (190,192,193). However, no significant differences in cardiometabolic systems, body composition or neurochemical levels (e.g., BDNF, IL-6 and TNF-α) were found in PULSAR studies (191,(194)(195)(196)(197). Double-blind clinical studies revealed no beneficial effect of adjunctive sarcosine in drug-free schizophrenia patients or patients treated with clozapine (186,187,199).…”
Section: Indirect Modulation Of Nmdar Functions By Targeting Astrocytic Glyt1mentioning
confidence: 97%
“…Several studies investigated sarcosine augmentation efficacy in schizophrenia patients [ 224 , 225 , 312 , 347 , 350 , 352 , 353 , 354 ]. The addition of sarcosine (2 g/day) to antipsychotic medications, including risperidone [ 350 ] and other atypicals [ 225 ] but not clozapine [ 347 ], was found to benefit schizophrenia patients.…”
Section: Other Modulators Of the Glycine B Site At Nmdarmentioning
confidence: 99%